Anti‐CRLF2 Antibody‐Armored Biodegradable Nanoparticles for Childhood B‐ALL. (27th February 2013) - Raghunathan, Rekha; Mahesula, Swetha; Kancharla, Kranthi; Janardhanan, Preethi; Jadhav, Yeshwant L. A.; Nadeau, Robert; Villa, German P.; Cook, Robert L.; Witt, Colleen M.; Gelfond, Jonathan A. L.; Forsthuber, Thomas G.; Haskins, William E.
<x xml:space="preserve">Abstract</x> B‐precursor acute lymphoblastic leukemia (B‐ALL) lymphoblast (blast) internalization of anti‐cytokine receptor‐like factor 2 (CRLF2) antibody‐armored biodegradable nanoparticles (AbBNPs) are investigated. First, AbBNPsaere synthesized by adsorbing anti‐CRLF2 antibodies to poly(D, L‐lactide‐co‐glycolide) (PLGA) nanoparticles of various sizes and antibody surface density (Ab/BNP) ratios. Second, AbBNPs are incubated with CRLF2‐overexpressing (CRLF2+) or control blasts. Third, internalization of AbBNPs by blasts is evaluated by multicolor flow cytometry as a function of receptor expression, AbBNP size, and Ab/BNP ratio. Results from these experiments are confirmed by electron microscopy, fluorescence microscopy, and Western blotting. The optimal size and Ab/BNP for internalization of AbBNPs by CRLF2+ blasts is 50 nm with 10 Ab/BNP and 100 nm with 25 Ab/BNP. These studies show that internalization of AbBNPs in childhood B‐ALL blasts is AbBNP size‐ and Ab/BNP ratio‐dependent. All AbBNP combinations are non‐cytotoxic. It is also shown that CD47 is very slightly up‐regulated by blasts exposed to AbBNPs. CD47 is "the marker of self" overexpressed by blasts to escape phagocytosis, or "cellular devouring", by beneficial macrophages. The results indicate that precise engineering of AbBNPs by size and Ab/BNP ratio may improve the internalization and selectivity of future biodegradable nanoparticles for the treatment of leukemia patients, including drug‐resistant minority children and Down's syndrome patients with CRLF2+B‐ALL.